Identifying the contribution of occupational therapy in meeting the needs of women survivors of breast cancer - Keesing, Sharon; Rosenwax, Lorna; McNamara, Beverley (The College of Occupational Therapists - UK, 2018)
© 2018, The Author(s) 2018. Introduction: Little is known about how occupational therapy could assist women survivors of breast cancer and their partners who experience activity and role limitations during survivorship. This study sought to obtain views and consensus among occupational therapists regarding their potential role and the barriers and enablers to this potential service. Method: We used a three-round classical Delphi process to determine the views of occupational therapists (n = 40), and sought consensus (70%) for 49 statements concerning barriers and enablers affecting occupational therapy service provision during survivorship. Thematic analysis was used to determine themes and descriptive statistics to determine consensus level and median for statements. Findings: Forty-six statements showed consensus. Themes identified were: (a) women and partners experience unmet needs; (b) gaps exist regarding supportive care; (c) access to comprehensive survivorship support is required; (d) barriers to occupational therapy exist; and (e) occupational therapists offer many supports to improve activity and role engagement for women and partners. Conclusion: Occupational therapy is well-positioned to affect improvements in occupational engagement and role participation for women survivors of breast cancer and their partners. However, many barriers are identified. Occupational therapists must advocate the value of occupational therapy during survivorship to facilitate women’s engagement in meaningful activities and roles.